(5x+1)2=(3x+5)2
<=> (5x+1)2-(3x+5)2=0
<=> (5x+1+3x+5)(5x+1-3x-5)=0
<=> (8x+6)(2x-4)=0
\(\Leftrightarrow\orbr{\begin{cases}8x+6=0\\2x-4=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}8x=-6\\2x=4\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=-\frac{3}{4}\\x=2\end{cases}}\)
Vậy......
\(\left(5x+1\right)^2=\left(3x+5\right)^2\)
\(\Leftrightarrow\orbr{\begin{cases}5x+1=3x+5\\5x+1=-3x-5\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}2x=4\\8x=-6\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=2\\x=\frac{-3}{4}\end{cases}}\)